Accumulation of and Response to Auxins in Roots and Nodules of the Actinorhizal Plant Datisca glomerata Compared to the Model Legume Medicago truncatula - Demina, Irina V.; Maity, Pooja Jha; Nagchowdhury, Anurupa; Ng, Jason L. P.; van der Graaff, Eric; Demchenko, Kirill N.; Roitsch, Thomas; Mathesius, Ulrike; Pawlowski, Katharina (Frontiers in Plant Science, 2019)
Auxin- and cytokinin profiles were examined in roots and nodules of a legume, Medicago truncatula, and an actinorhizal species, Datisca glomerata. The auxin response in roots and nodules of both species was analysed in hairy root system obtained by transformation with Agrobacterium rhizogenes carrying a beta-glucuronidase gene under control of the synthetic auxin-responsive promoter DR5. The effects of two different auxins on root development were compared for both species during growth in vitro. For both species, the auxin present in nodules at the highest levels was phenylacetic acid (PAA). No differences were found between the concentrations of active auxins of roots and nodules of D. glomerata, while the composition of active auxins differed between roots and nodules of M. truncatula. For both auxins and cytokinins, concentrations of the glycosylated forms were dramatically increased in nodules compared to roots of D. glomerata, an effect not found for M. truncatula. In contrast with the results on auxin levels, the auxin response as shown by the activation of DR5 promoter activity seemed significantly reduced in nodules compared to roots of both species, suggesting the accumulation of auxins in cell types that do not express the signal transduction pathway that leads to DR5 activation. The effect on root development was analyzed for the synthetic auxin naphthaleneacetic acid (NAA) and for the dominant endogenous auxin of nodules, PAA, in both species. The two auxins had similar effects, except that the sensitivity of root growth and –branching to PAA was lower than to NAA. However, while the effect of both hormones on primary root growth was the same for both plant species, effects on root branching were different: both auxins had the classical positive effect on root branching for M. truncatula, but a purely negative effect on D. glomerata. Such a negative effect of exogenous auxin on root branching has previously been found for two cucurbits that form lateral root primordia in the meristematic region of the parental root, squash and cucumber; however, root branching in D. glomerata does not follow that pattern.